Depression, anxiety and stress among patients with dialysis and the association with quality of life - Bujang, Mohamad A.; Musa, Ramli; Wen Jiun, Liu; Thian Fook, Chew; Lim, Christopher T.S.; Morad, Zaki (Elsevier, 2015)
Studies addressing the nature of relationship between psychological symptoms and quality of life among dialysis patients in Malaysia are scarce. Hence, this study is intended to investigate the association between psychological symptoms such as depression, anxiety and stress on the quality of life in dialysis patients. A cross sectional multicentre study was conducted from May to October 2012 at 15 centres that provide haemodialysis and/or peritoneal dialysis. Apart from socio-demographic profile data collection, WHOQOL-BREF and DASS21 questionnaires were administered to study subjects. All three psychological symptoms had significant impact on quality of life domains of physical health, psychological health, social impact, perceived environment and overall quality of life. These findings suggest that subjects with symptoms of depression, anxiety and stress had poorer quality of life than those without, highlighting the negative impact of psychological symptoms.